Pencitraan Rembesan Limbah Menggunakan Metode Geolistrik Resistivity Konf igurasi Schlumberger 2-dimensi - Agus Suprianto (Universitas Trunojoyo Madura, 2008)
Resistivity imaging has been done to identify of thewaste leakage on the sand horizontally and vertically. Schlumberger configuration with 5 cm electrode spacing was used. For the interpretation, we used iteration methods on Res2Dinv software. Finally, the waste leakage can be displayed clearly, that indicated with smaller specific resistancefrom surrounding